The Fund's Financing Role : Reform Proposals on Liquidity and Emergency Assistance. (Policy Papers; Policy Paper, 2011)
The possible global repercussions from the ongoing turmoil in the Euro Area and recent calls for enhanced emergency assistance in the Middle East and North African region are reminders of the urgent need for a more effective global financial safety net to deal with increased interconnectedness and volatility. Past work by staff identified gaps in the Fund's lending toolkit to respond to liquidity needs of members with relatively strong fundamentals affected during systemic crises (the crisis bystanders), and to address urgent financing needs arising in a broader range of circumstances than natural disasters and post-conflict situations. The companion paper on the Review of the Flexible Credit Line (FCL) and Precautionary Credit Line (PCL) also identified gaps in the overall flexibility of the financing toolkit. This paper provides proposals to fill these gaps, while preserving the simplicity and coherence of the lending framework, and balancing members' financing needs against the need for adequate safeguards for the use of Fund resources.